The front runner : the life of Steve Prefontaine - O'Meara, Brendan (Mariner Books, 2025)
"In the fifty years since his tragic death in a car crash, Steve Prefontaine has towered over American distance running. One of the most recognizable and charismatic figures to ever run competitively in the United States, Prefontaine has endured as a source of inspiration and fascination-a talent who presaged the American running boom of the late 1970s and helped put Nike on the map as the brand's first celebrity-athlete face. Now on the anniversary of his untimely death, author Brendan O'Meara, host of the Creative Nonfiction podcast, offers a fresh, definitive retelling of Prefontaine's life, revisiting one of the most enigmatic figures in American sports with a twenty-first-century lens. Through dozens of original interviews with family, friends, teammates, and competitors, this long-overdue reappraisal of Prefontaine-the first such exhaustive treatment in almost thirty years-provides never-before-told stories about the unique talent, innovative mental strength, and personal struggles that shaped Prefontaine on and off the track. Bringing new depth to an athlete long eclipsed by his brash, aggressive running style and the heartbreak of his death at twenty-four, O'Meara finds the man inside the myth, scrutinizing a legacy that has shaped American sports culture for decades. What emerges is a singular portrait of a distinctly American talent, a story written in the pines and firs of the Pacific Northwest back when running was more blue-collar love than corporate pursuit-the story of a runner whose short life casts a long, fast shadow"--